Efficacy of native bio-control agents on soil microflora, dry root rot incidence and seed yield of rainfed arid crops - RITU MAWAR, SATISH LODHA* and (Indian Phytopathology, 2010)
Effectiveness of four bio-control agents viz., Trichoderma harzianum, Aspergillus versicolor, Penicillium oxalicum and Bacillus firmus, isolated from arid soils, was tested on total microbial population, incidence of dry root rot and seed yield of cowpea, guar and sesame. T. harzianum, A. versicolor and P. oxalicum were amended in soil along with farm yard manure while B. firmus was coated on seeds. Maximum reductions in the population of total fungi and bacteria were recorded in P. oxalicum amended soil at both the sampling times. However, total actinomycetes reduced more in A. versicolor amended soil and B. firmus treated plots in guar and cowpea, respectively.The bio-control agents significantly reduced the incidence of dry root rot resulting in increased yield of all the three crops. B. firmus and A.versicolor were found more effective in overall performance than other bio-control agents.